Prophet of peace: prophet Muhammad for little hearts - Khan, Nafees (Goodword Books India, 2002)
This children's book introduces young readers to the life and teachings of Prophet Muhammad in a simple and age-appropriate manner. It highlights his compassion, kindness, and peaceful nature, fostering positive values and respect for diversity.